The little wartime library - Thompson, Kate, 1974- (Forever, 2023)
"London, 1944: Clara Button is no ordinary librarian. While war ravages the city above her, Clara has risked everything she holds dear to turn the Bethnal Green tube station into the country's only underground library. Down here, a secret community thrives with thousands of bunk beds, a nursery, a café, and a theater-offering shelter, solace, and escape from the bombs that fall upon their city. Along with her glamorous best friend and assistant Ruby Munroe, Clara ensures the library is the beating heart of life underground. But as the war drags on, the women's determination to remain strong in the face of adversity is tested to the limits when it may come at the price of keeping those closest to them alive"--